2003
DOI: 10.2298/hel0339155h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salinity stress on seed yield through physiological parameters in sunflower genotypes

Abstract: Sunflower is an important oilseed crop grown under rain-fed situation during winter/summer seasons in Northern Karnataka, India. Most of rain-fed areas have salinity problem resulting in poor yields of sunflower crop. An effort was made to screen available sunflower germplasm against graded salinity levels and relate their yield performance to various physiological parameters. Among the genotypes tested, PAC-36 recorded the highest seed yield (20.9 q/ ha) followed by KBSH-1 (19.65 q/ha), MSFH-17 (17.5 q/ha) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
2
6
0
2
Order By: Relevance
“…Also in line with our results, Francois (1996) and Bybordy (2010) reported that seed yield of sunflower and canola cultivars were reduced with increasing salinity level, respectively. Moreover, Hebbara et al (1992) and Hebbara et al (2003), also in line with our results reported that yield of all of sunflower cultivars decreased as salinity levels increased in the field. In the pot experiment, Hebbara et al (2003) showed that leaf temperature, stomata conductance and transpiration rate reduced, but osmotic potential increased under salinity.…”
Section: Seed Yieldsupporting
confidence: 92%
See 1 more Smart Citation
“…Also in line with our results, Francois (1996) and Bybordy (2010) reported that seed yield of sunflower and canola cultivars were reduced with increasing salinity level, respectively. Moreover, Hebbara et al (1992) and Hebbara et al (2003), also in line with our results reported that yield of all of sunflower cultivars decreased as salinity levels increased in the field. In the pot experiment, Hebbara et al (2003) showed that leaf temperature, stomata conductance and transpiration rate reduced, but osmotic potential increased under salinity.…”
Section: Seed Yieldsupporting
confidence: 92%
“…Moreover, Hebbara et al (1992) and Hebbara et al (2003), also in line with our results reported that yield of all of sunflower cultivars decreased as salinity levels increased in the field. In the pot experiment, Hebbara et al (2003) showed that leaf temperature, stomata conductance and transpiration rate reduced, but osmotic potential increased under salinity. They concluded that a large genetic variation existed among tested cultivars to salinity and they responded differently to salinity.…”
Section: Seed Yieldsupporting
confidence: 92%
“…Improvements in antioxidant potential alleviate oxidative stresses. Phenolics are important phytochemical components with significant antioxidant potential (Hebbar et al 2003). Foliar spray of pea plants with nutrients had improved the phenolic compounds content (Lingyun et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…High concentrations of dissolved salts in the soil and root zone can cause the high osmotic pressure and, thus, water availability is reduced. These conditions affect physiological activities and subsequently crop yield since plants will need to spend more energy to obtain water (Hebbara et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…alt stress is one of the most important abiotic stresses in arid and semiarid regions (Ashraf and Harris, 2004;Hebbara et al, 2003). Plants under stress have less dry matter, leaf area (Amirjani, 2011) and yield.…”
mentioning
confidence: 99%